Spatiotemporal processing of neural cell adhesion molecules 1 and 2 by BACE1 in vivo - Kim, WonHee (J Biol Chem, 2021)
Neural cell adhesion molecules 1 (NCAM1) and 2 (NCAM2) belong to the cell adhesion molecules of the immunoglobulin superfamily and have been shown to regulate formation, maturation, and maintenance of synapses. NCAM1 and NCAM2 undergo proteolysis, but the identity of all the proteases involved and how proteolysis is used to regulate their functions are not known. We report here that NCAM1 and NCAM2 are BACE1 substrates in vivo. NCAM1 and NCAM2 overexpressed in HEK cells were both cleaved by metalloproteinases or BACE1, and NCAM2 was also processed by γ-secretase. We identified the BACE1 cleavage site of NCAM1 (at Glu 671) and NCAM2 (at Glu 663) using mass spectrometry and site-directed mutagenesis. Next, we assessed BACE1-mediated processing of NCAM1 and NCAM2 in the mouse brain during aging. NCAM1 and NCAM2 were cleaved in the olfactory bulb of BACE1+/+ but not BACE1−/− mice at postnatal day 10 (P10), 4 and 12 months of age. In the hippocampus, a BACE1-specific soluble fragment of NCAM1 (sNCAM1β) was only detected at P10. However, we observed an accumulation of full-length NCAM1 in hippocampal synaptosomes in 4-month-old BACE1−/− mice. We also found that polysialylated NCAM1 (PSA-NCAM1) levels were increased in BACE1−/− mice at P10 and demonstrated that BACE1 cleaves both NCAM1 and PSA-NCAM1 in vitro. In contrast, we did not find evidence for BACE1-dependent NCAM2 processing in the hippocampus at any age analyzed. In summary, our data demonstrate that BACE1 differentially processes NCAM1 and NCAM2 depending on the region of brain, subcellular localization, and age in vivo.